Infrastructured Timescapes of the Anthropocene and Climate Change - Claudio Coletta (Tecnoscienza)
This introduction aims to frame the main contents of the special issue and offers an overview of the collected contributions. It discusses key conceptual themes and reflects on how an infrastructural and temporal approach can open new understandings of climate politics. The core argument inspiring the special issue is threefold. First, the Anthropocene and Climate Change form distinctive “timescapes” that shape knowledge and politics in specific ways. Second, these timescapes are infrastructured, with infrastructure serving both as a key site for producing, organizing and extracting time and as an analytical category to look at temporal work. Finally, because the Anthropocene and Climate Change are temporally infrastructured, efforts at adaptation and mitigation are subject to time leaks, glitches, delays, accelerations, invisibility and performativity that affect time horizons. The introduction stresses the importance of keeping together a pragmatic, critical and speculative approach. It concludes by reflecting on how an infrastructural and temporal approach can shed light on the hegemonic frames shaping climate governance, and open up possibilities for alternative climatic regimes and political action.